2013
DOI: 10.1089/zeb.2012.0792
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measurement of Steroid Hormones in Zebrafish Holding-Water

Abstract: Zebrafish (Danio rerio) has recently emerged as a new animal model in neuroendocrinology and behavior (e.g., stress physiology and ecotoxicology studies). In these areas, the concentrations of steroid hormones in the blood are often used to study the endocrinological status of individuals. However, due to the small body size of zebrafish, blood sampling is difficult to perform and the amount of plasma obtained per sample for assaying hormones is very small (ca. 1-5 lL), and therefore most studies have been usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Overall, WC release rates, which provide a surrogate for blood cortisol concentrations (Félix et al 2013;Friesen et al 2012;Gabor and Contreras 2012;Wong et al 2008), were directly proportional to the estimated concentration of WWTW effluent at these sites. Female sticklebacks translocated from the same sites five months previously and subsequently held in pristine aquarium conditions continued to exhibit the same site-related trends in WC release rates as their more recently wild-caught counterparts.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Overall, WC release rates, which provide a surrogate for blood cortisol concentrations (Félix et al 2013;Friesen et al 2012;Gabor and Contreras 2012;Wong et al 2008), were directly proportional to the estimated concentration of WWTW effluent at these sites. Female sticklebacks translocated from the same sites five months previously and subsequently held in pristine aquarium conditions continued to exhibit the same site-related trends in WC release rates as their more recently wild-caught counterparts.…”
Section: Discussionmentioning
confidence: 96%
“…Instead, the magnitude of the stress response was measured indirectly via the release of cortisol across the gill epithelium to the surrounding water (Scott and Ellis 2007) the rate of which varies in proportion with blood cortisol concentrations (Félix et al 2013;Friesen et al 2012;Gabor and Contreras 2012;Wong et al 2008). During March 2014 five fish were transferred by handnet from a holding tank to a bucket containing 5 litres of water in which they remained for 30 mins before being transferred to individual Nalgene tubs (150 ml, 6.5 cm diameter, with screw-fit lids) containing 100 ml of artificial freshwater (deionised water containing 0.33 g/l aquarium grade sea salt; Klüttgen et al 1994).…”
Section: Assessment Of Stress Responsiveness In the Translocated Aquamentioning
confidence: 99%
“…The rate of release of steroids, from the bloodstream to the surrounding water, across the gill epithelium of fish has been shown to be proportional to the steroid concentration in the blood during the period of collection (Félix et al, 2013;Scott and Ellis, 2007;Sebire et al, 2007) and CRTW estimates may therefore provide a more functionally relevant assessment of HPI activity than WBIC. The cortisol release rates recorded in the present study (100 -3500 pg/g/h) are within the range reported previously for this species (Fürtbauer et al, 2015a;Sebire et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it may be erroneous to assume that the quantity of steroid lost across the gills should be directly proportional to that accumulating in other tissues -diffusional losses across the gills are presumably a function of blood cortisol concentration, and will not necessarily reflect rates of steroid synthesis and metabolism occurring elsewhere in the fish which will, however, affect whole-body concentrations. Few data are available to help interpret these observations since different stress axis endpoints are rarely measured simultaneously in the same individual but a lack of consistent proportionality between WBIC and CRTW in the same individuals has been reported for guppies (Poecilia reticulata) held under laboratory conditions (Fischer et al, 2014) and differences in the relationship between plasma cortisol and CRTW has been reported between the sexes for zebrafish (Danio rerio; Félix et al, 2013) and in the daffodil cichlid (Neolamprologus pulcher; Ligocki et al, 2015). It may also be pertinent that in 18 zebrafish gills cortisol is converted via cortisone to 20β-hydroxycortisone (Tokarz et al, 2012) and in stressed zebrafish the concentrations of sulphated and glucuronidated 20β -hydroxycortisone release across the gills were found to be an order of magnitude greater than the corresponding conjugates of cortisol (Tokarz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation